Wap e-mail system (wapes) / Tan Wang Wee - Tan, Wang Wee (2003)
This project is to build an application based on WAP (Wireless Application Protocol), where users could check their e-mails via their WAP phone. The objective of this project is to provide mobile users with the facility to check their e-mails while on the move. As such, users would be required to create a login account on the e-mail service created, which is accessible via the World Wide Web or through WAP phones. This project is divided into two modules- the Web Module and WAP Module. The Web Module is an e-mail service site, allowing users to sign up for e-mail accounts, or for existing users to login to their accounts. Users would be able to perform typical e-mail functions on this module. On the other hand, the WAP Module allows WAP users to use their WAP browsers on their mobile phones to check their e-mails. They could also perform typical e-mail functions via their WAP phones. This means that mobile users do not need to look for Internet connected PCs to check their important e-mails. They could simply check their e-mails via their WAP phones at anytime and anywhere according to their convenience